The Effect of Inflation, Provincial Minimum Wage (UMP) and GRDP on Trade Balance in Java Island - Trisna Wandira; Purmini Purmini (Journal of Research in Social Science and Humanities, 2024)
This research studies the effect of inflation, UMP, and GRDP on the trade balance of Java Island by considering the complexity of the relationship between these variables. The methodology used is multiple linear regression analysis with secondary data from the Central Bureau of Statistics and the Ministry of Trade for the period 2017-2023. The Common Effect Model (CEM) is used, and the results of the analysis show that the independent variables can explain 72.28% of the variation in the trade balance. The results show that inflation has a significant negative effect on the trade balance, where an increase in inflation can reduce the competitiveness of domestic products. UMP also has a significant and negative effect, where an increase in UMP may increase purchasing power but also production costs, potentially reducing competitiveness. In contrast, GRDP shows a significant positive effect, where economic growth can increase export volume despite the risk of increasing imports. This study recommends the need for effective economic policies to control inflation and adjust UMP to suit local economic conditions, in order to improve Indonesia's trade balance performance.